Paul Éluard y César Vallejo: de la vanguardia a la fraternidad universal - Fernández Cozman, Camilo Rubén (2018)
Both Paul Éluard and César Vallejo went through an avant-garde period and went on to write politically-committed poetry where the theme of universal brotherhood was developed. Both poets were influenced by the Spanish Civil War and highlighted how solidarity can defeat death. This article compares two books: España, aparta de mí este cáliz and Au rendez-vous Allemand, in which Éluard and Vallejo respectively emphasize the theme of brotherhood among men.